2005
DOI: 10.1016/j.applthermaleng.2004.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of geometrical parameters on heat transfer and pressure drop characteristics of plate fin and tube heat exchangers

Abstract: In this study, the influences of the changes in fin geometry on heat transfer and pressure drop of a plate fin and tube heat exchanger are investigated, numerically. A computational fluid dynamics (CFD) program called Fluent is used in the analysis. The segment of one tenth of fin is used in the modeling, due to symmetrical condition. The results of heat transfer, static, and total pressure drop values of ten different fins are tabulated and the normalized values of them are, also, given for the comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 14 publications
3
36
1
2
Order By: Relevance
“…These results are consistent with the findings given in the studies of Kim and Song [5] and Erek et al [6]. However, the enhancement in heat transfer is found to be valid up to a certain value.…”
Section: The Effect Of Fin Tube Location and Ellipticitysupporting
confidence: 83%
See 1 more Smart Citation
“…These results are consistent with the findings given in the studies of Kim and Song [5] and Erek et al [6]. However, the enhancement in heat transfer is found to be valid up to a certain value.…”
Section: The Effect Of Fin Tube Location and Ellipticitysupporting
confidence: 83%
“…The experiments reveal that when the tube is placed in a downstream position and when the gap between the fins is decreased, better heat transfer is accomplished. Erek et al [6] performed a numerical study for a plate fin heat exchanger with one row tube configuration and fixed flue gas mass flow rate. They observed heat transfer enhancement when the distance between fins is decreased, when the fin tube is shifted to downstream region, when the fin height is increased, when thin fins are used and when elliptical tubes replace circular ones.…”
Section: Introductionmentioning
confidence: 99%
“…By having tested fourteen samples Rich [2][3] then reported that under the experimental range the intensity of heat transfer did not depend on the fin pitch and the pressure drop per tube was independent of the number of tube rows. McQuiston [4,5] Considerable efforts on numerical studies of plain fin-and-tube heat exchangers were reported in [12][13][14][15][16][17]. Bestani et al [18] earlier conducted three-dimensional simulations on pattern of flow passing around a cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…From the field synergy principle point of view, they analyzed the mechanism of heat transfer enhancement for describing their numerical results. Erek et al [17] used CFD to study the effects of geometrical parameters on performance of plain fin-and-tube heat exchangers with flat tubes, and they suggested that the increase 9 of ellipticity could increase the heat transfer together with a distinct decrease of the pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…Franco and Giannini [4] analysed plate-fin heat exchangers using analysis of counter-flow heat exchangers and compact heat exchangers. Erek et al [5] numerically studied the effect of changing pressure drop and heat transfer in geometry of blade in the plate finned tube heat exchanger. Durmus et al [6] experimentally investigated the heat transfer plates for three different surface geometry, friction factor and energy losses.…”
Section: Introductionmentioning
confidence: 99%